Ethnopharmacology and phenology of high-altitude medicinal plants in Kashmir, Northern Himalaya - Mir, Abrar Yousuf; Yaqoob, Umer; Hassan, Musheerul; Bashir, Faiza; Bin Zanit, Seema; Haq, Shiekh Marifatul; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2021)
Background: Traditional knowledge plays an important role in the conservation of floral diversity and is often used for the treatment of numerous diseases in local medicinal systems. Diverse cultural groups in the Himalayan regions have their own local indigenous healthcare systems, with medicinal plant applications that differ depending on geography and ecology. Therefore, it is important to understand plant ecological behavior for prioritizing conservation efforts and comprehending the impact of climate change on plant phenological traits. Methods: Ethnopharmacological data was collected through interviews and group discussions using semi-structured and close-ended questionnaires from different ethnic groups i.e., Gujjar, Bakarwal, and Kashmiri. The data was subjected to hierarchical cluster analysis and ordination techniques (Principal Component Analysis) using multivariate software. Results: The present investigation documented a total of 32 plant species belonging to 31 genera in 23 families. Across the 23 families, the distribution of species was unequal, half of the species belonged to just 6 families (Asteraceae, Berberidaceae, Lamiaceae, Ranunculaceae, Solanaceae and Amaranthaceae) while the remaining half belonged to 17 families. Amongst the parts of plants, roots were the most utilized plant part with 25% of usage followed by whole plant (22%). Gastro-intestinal disorders were treated with most species (18%), followed by pulmonary infections (13%). A heat map showed two distinctly separated clusters based on the degree of intensity of flowering timing of the flora and month. Based on the conservation assessment, out 19% of all species observed fell in the Critically Endangered category of IUCN, followed by 6% in the Vulnerable category. Conclusions: This study provides the ethnopharmacological and ecological scope of the plants of the Kashmir in the northern Himalaya. There is need to develop strategies to conserve and sustainably harvest these plants in order to maintain their long-term benefits in the medicinal field. Key words: Flowering time; Disease cured; Conservation; Kashmir